Cataloghi per un’esposizione: Gaio e l’‘arte’ di insegnare il diritto a Roma - Battaglia, Federico (Tesserae iuris, 2024)
Ferdinando Bona contributed to stabilizing the historiographical turn that Manfred Fuhrmann imprinted on Gaian studies (the Institutiones belong to the ancient ‘systematic manual’ literary genre). Bona suggested that the role of diairetical patterns should be redefined. Within the ‘expository system’ of the Institutiones, Gaius' divisiones appear today as a functional tool for the composition of the text and the transmission of information to the reader, like other text organization tools. Among these instruments is the listing, with which the author of a text orders an articulated set of legal information. Confines between listing and division are blurred, and their expository use closely reflects the techniques used for argumentative purposes by Roman jurisprudence. This essay addresses the listings within the text of the Institutiones and the various ways they were used, thus fitting into Bona's research line.